Mechanism for the SNAr reaction of atrazine with endogenous thiols: experimental and theoretical study. (2nd October 2017) - Calfumán, K.; Gallardo-Fuentes, S.; Contreras, R.; Tapia, R. A.; Campodónico, P. R.
Abstract : The mechanism for the SN Ar reaction of atrazine with endogenous thiols: a stepwise or concerted process? Abstract : The reaction mechanism in aromatic nucleophilic substitution reactions is discussed using kinetic study complemented with quantum chemical calculations. The model system is the reaction of a series of biothiols toward atrazine (ATZ) in aqueous media. The proposed reaction mechanism discloses a non-catalyzed pathway and the presence of a deprotonated (thiolate) nucleophile in water suggests that the reaction mechanism is borderline between a stepwise route and a concerted process. The full analysis of the potential energy surface reinforces the addition/elimination mechanism. Despite numerous attempts to locate transition structures associated with the leaving group departure, they were unsuccessful, presumably because this step is extremely fast.